(untitled) (Tokyo, 1991)
This book offers methods for analysing foods, the organization and content of food composition tables and data bases, and procedures for the accurate international interchange of data-focuses specifically on the issues involved gathering, and estimating where necessary, the data for such tables and data bases
Keywords: Food,Food; Analysis,Composition